Anaplastic Large Cell Lymphoma in Central America: A Report From the Central American Association of Pediatric Hematology Oncology (AHOPCA). Issue 1 (8th August 2015) - Ceppi, Francesco; Ortiz, Roberta; Antillón, Federico; Vasquez, Roberto; Gomez, Wendy; Gamboa, Jessica; Garrido, Claudia; Chantada, Guillermo; Peña, Armando; Gupta, Sumit
Abstract : Background: Although anaplastic large cell lymphoma (ALCL) is curable in high‐income countries (HIC), data from low‐ and middle‐income countries (LMIC) are lacking. We therefore conducted a retrospective study of the Central American Association of Pediatric Hematology Oncology (AHOPCA) experience in treating ALCL. Procedure: We included all patients age <18 years newly diagnosed with ALCL treated between 2000 and 2013 in seven AHOPCA institutions. Retrospective data were extracted from the Pediatric Oncology Network Database. Results: Thirty‐one patients met inclusion criteria. Twenty‐five (81%) had advanced disease (stages III and IV), six (19%) were treated on the APO (doxorubicin, prednisone, vincristine) regimen, 15 (49%) on multi‐agent chemotherapy designed for T‐cell lineage malignancies (GuatALCL protocol), and 10 (32%) on BFM‐based treatment regimens. Five‐year overall event‐free survival and overall survival were, respectively, 67.1 ± 8.6% and 66.7 ± 8.7%. All 10 events occurred in patients treated on BFM‐based treatment regimens or the GuatALCL protocol, none on APO treatment: two patients experienced relapse, six treatment related mortality (TRM), and two abandonment. Conclusions: Treatment of ALCL in countries with limited resources is feasible with similar outcomes as in HIC, though the causes of treatment failure differ. Less intensive regimens may be preferable in order to decrease TRM and improve outcomes. Prospective clinical trials determining the ideal treatment for LMIC children with ALCL are necessary. Pediatr Blood Cancer © 2015 Wiley Periodicals, Inc.